Educommunication and transmedia narrative in the development of digital critical thinking. - Matamoros Dávalos, Ángel Alberto; Avilés Pazmiño, Mariana Isaura; Urgilés Pineda, Mario Wilfrido (Scripta Mundi, 2025)
This work aims to analyze how the convergence between educommunication and transmedia narrative promotes digital critical thinking in students. Through a qualitative bibliographic review method, it is demonstrated that educommunication, by promoting participation and conscious use of the media, and transmedia narrative, by expanding stories on multiple platforms, cultivate analysis and decision-making skills in the digital environment. It is concluded that the combination of these approaches enriches the educational experience and forms critical and responsible citizens in the digital age. However, the need for a teaching intervention that guides the reflective use of technologies is emphasized, in order to guarantee the development of digital critical thinking in students.